Role of Reversal Learning Impairment in Social Disinhibition following Severe Traumatic Brain Injury. (12th January 2016) - Osborne-Crowley, Katherine; McDonald, Skye; Rushby, Jacqueline A.
Abstract: Objectives: The current study aimed to determine whether reversal learning impairments and feedback-related negativity (FRN), reflecting reward prediction error signals generated by negative feedback during the reversal learning tasks, were associated with social disinhibition in a group of participants with traumatic brain injury (TBI).Methods: Number of reversal errors on a social and a non-social reversal learning task and FRN were examined for 21 participants with TBI and 21 control participants matched for age. Participants with TBI were also divided into low and high disinhibition groups based on rated videotaped interviews.Results: Participants with TBI made more reversal errors and produced smaller amplitude FRNs than controls. Furthermore, participants with TBI high on social disinhibition made more reversal errors on the social reversal learning task than did those low on social disinhibition. FRN amplitude was not related to disinhibition.Conclusions: These results suggest that impairment in the ability to update behavior when social reinforcement contingencies change plays a role in social disinhibition after TBI. Furthermore, the social reversal learning task used in this study may be a useful neuropsychological tool for detecting susceptibility to acquired social disinhibition following TBI. Finally, that the FRN amplitude was not associated with social disinhibition suggests that reward prediction error signals are not critical for behavioral adaptation in the social domain. ( JINS, 2016, 21, 303–313)